2011
DOI: 10.1111/j.1472-765x.2010.02989.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of bovine serum albumin to improve the RT-qPCR detection of foodborne viruses rinsed from vegetable surfaces

Abstract: Aims:  To demonstrate that produce rinsates used for RT‐qPCR detection of foodborne viruses may cause significant PCR inhibition and propose a means to reduce its impact on sensitivity. Methods and Results:  Here, it is shown that rinsing and concentration from spinach and precut lettuce have the potential to generate RNA extracts that are inhibitory to RT‐qPCRs assembled from commercial kits for the detection of norovirus GII (NoV GII), hepatitis A virus (HAV), hepatitis E virus (HEV), rotavirus (RV) and feli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…Additional procedures have been developed and are still being improved, for the removal or reduction of the effects of PCR inhibitors such as tannic, humic and fulvic acids which are abundant in natural waters (Kreader 1996;Al Soud and Radstrom 2000;Guy et al 2003;Skotarczak 2009;Plante et al 2011;Schriewer et al 2011). In our studies, the differences between the nested PCR signals and C T values obtained for the DNA of oocysts recovered from lake and from distilled water implicate the presence of inhibitors in environmental water.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Additional procedures have been developed and are still being improved, for the removal or reduction of the effects of PCR inhibitors such as tannic, humic and fulvic acids which are abundant in natural waters (Kreader 1996;Al Soud and Radstrom 2000;Guy et al 2003;Skotarczak 2009;Plante et al 2011;Schriewer et al 2011). In our studies, the differences between the nested PCR signals and C T values obtained for the DNA of oocysts recovered from lake and from distilled water implicate the presence of inhibitors in environmental water.…”
Section: Discussionmentioning
confidence: 78%
“…Many chemicals are used to deactivate PCR inhibitors, e.g., acetamide, betaine, dextran, glycerol, formamide, pectinase, polyvinylpyrrolidene, aqueous solutions of non-fat dry milk or bovine serum albumin (BSA) (Al Soud and Radstrom 2000;Plante et al 2011). Earlier studies revealed that BSA is one of the most efficient facilitators of conventional PCR (Al Soud and Radstrom 2000;Skotarczak 2009;Plante et al 2011;Schriewer et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations